Marriage Women Select Careers: Indonesian Film Reception Analysis â€œDua Hati Biruâ€ (2024) - Afinada Aulia Agani; Triyono Lukmantoro (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
Film Dua Hati Biru (2024) lifts the drama's genre from the story of young women marrying and entering a conflicting reality of life and gender equality. The film forms the discussion room of both audiences and social media users. The study was intended to analyze the audiences' interpretation of the reception of family conflicts in the film, especially women who got married in their teen years. The study uses qualitative research methods with an encoding/decoding model reception approach and is a research phenomenon. Data is collected by conducting in-depth interviews, observations, and relevant library studies. Research shows the use of the Dua Hati Biru (2024) film audience as the dominant-hegemonic position and the dominant position. The dominant use of the audience is illustrated in the scene showing that women who marry young because they 'married by infants' then face conflicts and consequences that leave themselves with the choice to fully care for household or career affairs. Burial in a negotiating position occurred at scenes showing that caring for children and households was the wife's responsibility.